Optimalisasi Literasi dan Peningkatan Nilai Gizi Terhadap Masyarakat melalui X Banner - Pratiwi, Indah; Jannah, Rizky Mifthakul; Dyatin, Rochmad Nur; Handayani, Tri Mega; Dasmadi, Dasmadi (Edumedia Solution, 2023)
Some of the activities that have been carried out refer to the importance of literacy, increasing nutritional value by processing local food, as well as public services through x-banners. In this increasingly advanced era, the use of technology and social media has become an inseparabel part of the current generation’s daily life. This is a new challenge for the people in Tempursari Village, namely a lack of interest in reading and a lack of information for public services. The implementations of these work programs intends to stay in touch and collaborate with the people in Tempursari Village. The problems faced by the community include limited media. Students have made efforts to increase the knowledge and skills of the Tempursari Village community in literacy, local food processing, and the presentation of public service information through X Banners.